Swiftlet Sanctuary Surveillance: Integrating Temperature, Humidity, and Light Sensors for Enhanced Monitoring - Kamarudin, Farhan Najmi; Hazli Roslan (Progress in Engineering Application and Technology, 2024)
The surging demand for saliva-based nests in East Asia has led to increased swiftlet farming, despite challenges in manually monitoring swiftlet house conditions. This study introduces an automated monitoring system utilizing DHT11, LDR, and ESP32 microcontrollers. Real-time monitoring of temperature, humidity, and light levels aims to ensure an ideal swiftlet habitat. Integration with Blynk enables remote data access and timely notifications based on set thresholds. Project goals include creating a notification system for environmental changes, implementing an effective monitoring system, and displaying real-time data on an IoT platform. The project focuses on regular monitoring, web-based accessibility, and notification delivery. The use of DHT11, LDR, and ESP32 is expected to yield desired results, with data presented on a Blynk mobile app. The system alerts extreme values with a siren and LEDs. This project contributes to knowledge on swiftlet monitoring, aiding farmers in providing conducive environments, enhancing nest quality, and promoting ethical farming. The monitoring system, through remote access and notifications, safeguards nests, swiftlets, and encourages sustainable farming practices, potentially boosting profits in the Southeast Asian swiftlet farming sector.